Revision of Gymnotus (Gymnotiformes: Gymnotidae) from the Upper Madeira Basin of Bolivia and Peru, with descriptions of two new species - Craig, Jack M.; Correa-Roldán, Vanessa; Ortega, Hernán; Crampton, William G. R.; Albert, James S. (Zootaxa, 2018)
Banded Knifefishes (Gymnotus, Gymnotidae) comprise the most species-rich genus of Neotropical electric fishes, with 41 species currently described from throughout the humid Neotropics, from Mexico to Argentina. Despite substantial alpha-taxonomic work in recent years, the diversity of Gymnotus in some regions remains poorly understood. Here we describe the Gymnotus fauna of the Upper Madeira basin of Bolivia and Peru from examination of more than 240 adult specimens. Species are delimited and described using body proportions (traditional morphometrics), fin-ray, squamation and laterosensory-pore counts (meristics), quantitative shape differences (geometric morphometrics), osteological traits, and color patterns. Comparisons of standardized linear measures as well as multivariate statistical methods validate the presence in the Upper Madeira basin of three previously described species, two with wide-spread geographic distributions throughout Greater Amazonia (G. carapo and G. coropinae), and one (G. chaviro) endemic to southwestern Amazonia. We also diagnose and describe two new species that are endemic to the Upper Madeira basin: G. eyra n. sp., morphologically most similar to G. mamiraua from lowland Amazonia, and G. riberalta n. sp., morphologically most similar to G. pantanal from the Paraguay-Paraná basin. The five Gymnotus species from the Upper Madeira basin are not monophyletic, each species being more closely related to a different species from another region; i.e. the Gymnotus species from the Upper Madeira represents a polyphyletic assemblage. These descriptions to 43 the number of valid Gymnotus species.